2020
DOI: 10.1186/s13148-020-00908-3
|View full text |Cite
|
Sign up to set email alerts
|

AHRR cg05575921 methylation in relation to smoking and PM2.5 exposure among Taiwanese men and women

Abstract: Background: Polycyclic aromatic hydrocarbon (PAH)-rich substances like cigarette smoke and PM 2.5 induce aryl hydrocarbon receptor (AHR)-mediated aryl hydrocarbon receptor repressor (AHRR) methylation. AHRR cg05575921 and coagulation factor II (thrombin) receptor-like 3 (F2RL3) cg03636183 methylation patterns are well-established biomarkers for smoking. Even though AHRR cg05575921 methylation has recently been associated with PM 2.5 , the interaction between smoking and PM 2.5 on AHRR methylation is yet to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Similar to our findings, the association with cg05575921 in MESA remained significant after adjusting for self-reported smoking exposure, urinary cotinine, and other CVD risk factors, and remained significant in stratified analysis of former smokers and current smokers but not never smokers. Other studies have also reported evidence of cg05575921 differential methylation by air pollution in adults [ 62 ], by maternal smoking in neonates [ 63 , 64 ], and by smoking in atherosclerotic plaque specimens [ 65 ]. Similarly, cg09935388, located in the growth factor independent 1 transcriptional repressor gene ( GFI1 ) gene body region, has been found to be associated with smoking [ 32 , 66 , 67 ] and exposure to maternal smoking in fetuses [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, the association with cg05575921 in MESA remained significant after adjusting for self-reported smoking exposure, urinary cotinine, and other CVD risk factors, and remained significant in stratified analysis of former smokers and current smokers but not never smokers. Other studies have also reported evidence of cg05575921 differential methylation by air pollution in adults [ 62 ], by maternal smoking in neonates [ 63 , 64 ], and by smoking in atherosclerotic plaque specimens [ 65 ]. Similarly, cg09935388, located in the growth factor independent 1 transcriptional repressor gene ( GFI1 ) gene body region, has been found to be associated with smoking [ 32 , 66 , 67 ] and exposure to maternal smoking in fetuses [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second challenge to establishing a set point is variability in air quality. Studies from Taiwan have shown that air quality can have a small, but significant effect on cg05574921 levels 48 . However, the levels of air pollution in Taiwan are relatively low and fortunately, the level of PAH in the Midwestern United States are relatively low 49 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, increasing research proposes evaluating the methylation status in CpG sites related to smoking as a biomarker of smoking status [25,26,52,55,56,58,59]. Understanding the relationship between the epigenetic effects of smoking can increase our knowledge of the damage mechanisms that lead to chronic diseases related to tobacco smoking [14,23,[27][28][29][30][31]60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The level of methylation of cg05575921 is associated with asthma development in infants born to smoking mothers [24], impaired lung function, COPD development and exacerbations [25,26], and carcinogenesis [22,23,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%